Impact of oral azithromycin on recurrence of trachomatous trichiasis in Nepal over 1 year. Issue 8 (10th May 2006) - Zhang, H; Kandel, R P; Atakari, H K; Dean, D
Abstract : Background: Recently, a significant association between Chlamydia trachomatis infection and postoperative trachomatous trichiasis (TT) recurrence was shown. The current study evaluated whether azithromycin treatment at the time of surgery could reduce recurrence. Methods: As part of Nepal's national trachoma control programme, patients received azithromycin (53 patients) or placebo (56 patients) at surgery. Conjunctivae were graded for trachoma and swabbed to detect chlamydiae preoperatively and postoperatively up to 12 months. Logistic regression was performed for associations of treatment option with recurrence, infection, and active trachoma (by eye and by patient). Results: TT recurrence was 28.9% at 12 months. Recurrence was significantly lower for those with major TT at baseline in the azithromycin group at 12 months (p = 0.03); incident recurrence was also significantly lower at 6 months (OR, 0.056; 95% CI, 0 to 0.423; p = 0.004). There was a trend for increased recurrence among those with minor TT at baseline and for reduction of active trachoma and infection in the azithromycin group but not the placebo group. Conclusion: These data suggest that azithromycin treatment at the time of surgery may be warranted for patients with major TT. However, treatment should be investigated further for minor TT, for efficacy at subsequent time intervals and in other trachoma endemic settings.